Rotor parts for X-ray rotating anodes

The rotor part design for X-ray rotating anodes, featuring a heat-resistant carrier body and a transition zone-free thermal spray coating of Cu or Cu-based alloys, addresses the conductivity and material property issues of existing designs, achieving improved performance and adhesion.

JP2025511360AActive Publication Date: 2025-04-15PLANSEE SE
3 Cites 0 Cited by

Patent Information

Application Number
JP2024558965
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-06
Filing Date
2023-01-20
Publication Date
2025-04-15
Estimated Expiration
2043-01-20

AI Technical Summary

Technical Problem

Existing rotor parts for X-ray rotating anodes face challenges due to the formation of transition zones between copper or copper alloy coatings and ferromagnetic substrates, which lead to reduced conductivity and non-homogeneous material properties.

Method used

A rotor part design featuring a carrier body made of heat-resistant metals and a thermal spray coating of Cu or Cu-based alloys, where the microstructure lacks a transition zone at the connection surface, achieved through low-temperature gas spraying and subsequent annealing.

Benefits of technology

This solution enhances the conductivity of the rotor parts, improves adhesion strength, and allows for the application of coatings on complex geometries without the drawbacks of transition zones, resulting in rotor components with performance comparable to pure copper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511360000001_ABST
    Figure 2025511360000001_ABST
Patent Text Reader

Abstract

1. A rotor part for an X-ray rotating anode, comprising a carrier body and a thermal sprayed coating, the carrier body being made from one of the group of materials consisting of a heat-resistant metal, a heat-resistant metal-based alloy, Fe, an Fe-based alloy or a combination thereof, the thermal sprayed coating being made from Cu or a Cu-based alloy, the carrier body being material-bonded to the thermal sprayed coating in at least some parts at a connection surface, characterized in that the microstructure of the rotor part does not have a transition zone at the connection surface between the carrier body and the thermal sprayed coating.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rotor part for an X-ray rotating anode and a method for manufacturing the rotor part for an X-ray rotating anode. [Background technology]

[0002] The rotor for the X-ray rotating anode is rotatably mounted inside the vacuum housing and rotatably fixedly connected to the X-ray rotating anode. The rotor, together with the stator, forms an electric motor that rotates the X-ray rotating anode within the vacuum housing when the stator is connected to a power source. The rotor for the X-ray rotating anode usually consists of a copper cylinder surrounding a tubular iron core. The disadvantage of this is that the materials required for the electric drive have different thermal expansion coefficients, so they must be attached to each other in order to maintain a stable positioning of the rotor while surviving the temperature fluctuations that occur within the X-ray tube.

[0003] For example, from US Pat. No. 5,399,636 it is known to apply an outer rotationally symmetrical section of a rotor (for example made of copper) as a coating to an inner rotationally symmetrical section of a rotor (made of a ferromagnetic material, for example made of steel) to form a material bond between the two materials. In US Pat. No. 5,399,636 this is done by build-up welding, in particular by laser build-up welding. In laser build-up welding, the coating material is applied as a powder from a nozzle with a defined mass flow rate to the substrate and is then immediately melted by continuous exposure to laser light, thereby forming a welded joint with the substrate. However, this creates a boundary layer where the two materials are mixed (as the laser locally melts the substrate). This boundary layer represents a discontinuity in the properties of the respective materials. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] DE 19945414 A1

[0005] Rotor parts made of ferromagnetic materials (e.g. steel) with a coating of copper or copper alloys are currently mainly produced by backcasting. Backcasting is the metallurgical application of a material to a carrier body, whereby the carrier body is always in a solid agglomerated state for the process parameters used. For example, during backcasting, a solid bulk-shaped carrier body, for example made of steel, is inserted into a graphite mold. The carrier body is then backcast with a second material, for example consisting of a melt of copper or a copper alloy. For example, the melting point of pure copper is 1083°C. The targeted solidification of the molten copper or copper alloy makes it possible to realize largely non-porous interfaces or connection surfaces with good direct bonding of the copper or copper alloy to the carrier body. This means that no further joining surfaces have to be realized, as for example in the case of soldering. A disadvantage of this method, however, is the relatively high temperature of the molten metal acting on the substrate, in particular at the joining surface between the substrate and the coating. This high temperature leads to the formation of a transition zone between the copper or copper alloy coating and the substrate. The transition zone is formed in the copper or copper alloy applied by backcasting by melting or dissolving the substrate material, i.e. the material on the surface of the substrate is melted and diffuses into the coating, so that there is no homogeneous material property in the transition zone. In addition, individual components of the carrier body material (e.g. Fe) can diffuse beyond the transition zone into the coating and thus affect the material properties of the coating. After solidification of the copper or copper alloy, the cooled rotor part shows a microstructure (e.g. recognizable in a scanning microscope image of a cross section) consisting of the carrier body, the coating and the transition zone between the two materials. In the aforementioned backcasting process, after the molten copper or copper alloy solidifies, the coated rotor part is machined or reworked by turning, milling, cutting, etc. to the final part shape. This is called a "top-down" machining strategy.That is, the machining direction is "top to bottom" - subtractive from the top to the concrete - for example from a fully backcast part to the final part geometry by machining. The final geometry of the rotor part can only be realized in a rotationally symmetric manner due to the mechanical processing, since separate milling of non-rotationally symmetric shapes is very time-consuming and costly. Summary of the Invention [Problem to be solved by the invention]

[0006] It is an object of the present invention to provide an improved rotor part for an X-ray rotating anode, in particular one having improved electrical conductivity of both the coating and of the region of the connecting surface between the carrier body and the thermal spray coating. It is also an object of the present invention to provide an improved method for producing such a rotor part. [Means for solving the problem]

[0007] The technical problem of the present invention is solved by providing a rotor part for an X-ray rotating anode, comprising a carrier body and a thermal sprayed coating, the carrier body being made of a refractory metal, a refractory metal-based alloy, Fe, an Fe-based alloy or a combination thereof, the thermal sprayed coating being made of Cu or a Cu-based alloy, the carrier body being materially bonded to the thermal sprayed coating at least in some parts at the connection surface, characterized in that the microstructure of the rotor part has no transition zone at the connection surface between the carrier body and the thermal sprayed coating. Furthermore, a method for producing a rotor part having the features of claim 9 is provided. Advantageous further aspects of the present invention can be found in the dependent claims, which can be freely combined with one another.

[0008] The inventors have discovered that in the transition zone formed between the substrate and the coating during backcasting, the material properties of the binding partners are different. Furthermore, individual components of the substrate material may diffuse across the transition zone into the coating during backcasting and affect the material properties of the coating. These altered material properties have adverse effects when the rotor component is used (both in the transition zone and in the coating). In particular, the electrical conductivity of the copper or copper alloy in the coating produced by backcasting is reduced compared to a "pure" coating (made from copper or copper alloy), as is the electrical conductivity in the transition zone.

[0009] In the rotor component according to the invention, the electrical conductivity of copper can be fully utilized, since the electrical conductivity is not reduced by the presence of the dissolved carrier material in the thermal spray coating. Furthermore, the invention allows for a resource-saving use of copper or copper alloys, for example by applying the thermal spray coating directly with little or no post-treatment of the coating (a "bottom-up" approach of the process during processing, i.e. during processing or manufacturing, where the direction of action of the process is accumulation or addition "from bottom to top" by small units up to the final product, in contrast to the above-mentioned "top-down" processing strategy). Furthermore, the layer thickness of the thermal spray coating can be reduced (resource-saving) compared to the layer thickness in the backcasting process, and yet the rotor component according to the invention can achieve the same turning performance. Furthermore, the process according to the invention also allows for the application of Cu or Cu-based alloy coatings to more complex geometries or geometries for rotor components that do not necessarily have to be rotationally symmetric.

[0010] According to the invention, the rotor part comprises a carrier body and a thermal spray coating. In particular, the rotor part must be suitable for the X-ray rotating anode in order to withstand the loads in the X-ray tube. For example, no imbalances may occur. The rotor part may be a rotating part of the rotor which drives the X-ray rotating anode. However, the rotor part may also be a part of the rotor which is connected, for example by a material bond or a form fit, to another part in order to drive the X-ray rotating anode.

[0011] The carrier body is made of a material consisting of a refractory metal, a refractory metal-based alloy, Fe, an Fe-based alloy (including steel) or a combination thereof. The refractory metals are the refractory base metals of the 5th subgroup (vanadium, niobium and tantalum) and the 6th subgroup (chromium, molybdenum and tungsten). Their melting points are higher than that of platinum (1772°C). The refractory metal-based alloy can be understood as a combination of several pure refractory metals (e.g. W and Mo) as well as their alloys (e.g. W-Re) and / or their compounds. In the context of the present invention, the refractory metal-based alloy is understood to be an alloy containing at least 50% by weight, in particular at least 80% by weight, particularly preferably at least 90% by weight, of a refractory metal or several refractory metals. Among the refractory metals, Mo and W as well as Mo-based and W-based alloys are particularly suitable. In Mo-based or W-based alloys, the proportion of Mo (or W) is 50% by weight or more, preferably 80% by weight or more, in particular 90% by weight or more or 95% by weight or more. Molybdenum has a very high melting point, low thermal expansion and high thermal conductivity, which is why Mo or Mo-based alloys are particularly advantageous (also from the viewpoint of cost). Tungsten has the highest melting point of all metals, a very low thermal expansion coefficient and high dimensional stability. Carrier bodies made of a combination of steel and Mo with steel sections and Mo sections are particularly suitable from the viewpoint of cost.

[0012] An Fe-based alloy is understood to mean an alloy having more than 50% by weight Fe, in particular more than 80% by weight Fe, particularly preferably more than 90% by weight or more than 95% by weight Fe. In particular, steels having preferably more than 97% by weight Fe are advantageous for the carrier body according to the invention.

[0013] Thermal spray coatings according to the present invention are understood to be coatings applied by thermal spraying processes, such as plasma spraying (in air, in an inert gas or under low pressure), powder flame spraying, high velocity oxygen fuel (HVOF), detonation spraying (flame impact spraying), laser spraying and cold gas spraying (CGS). A common feature of all thermal spraying processes is the interaction of thermal energy with kinetic energy. The coating material is heated, for example with a spray torch (thermal energy) and / or accelerated to high velocities (kinetic energy). Particularly preferred coatings of the present invention are cold gas spray (CGS) coatings. An alternative embodiment is plasma spraying.

[0014] Low temperature gas spraying is a coating process in which powder particles are applied to a substrate with very high kinetic energy and low thermal energy.

[0015] The thermal spray coating is made of Cu or a Cu-based alloy. A Cu-based alloy is an alloy containing Cu, where Cu is the main component and the proportion of Cu is 50% by weight or more, preferably 70% by weight or more, particularly preferably 80% by weight or more. Examples of copper alloys include CuZn (Cu: copper, Zn: zinc), CuZnSi (Si: silicon), CuMg (Mg: magnesium), CuAl (Al: aluminum), CuBe (Be: beryllium), CuCrZr (Cr: chromium, Zr: zirconium) and CuZr. Cu or Cu alloys typically contain unavoidable impurities. In Cu or Cu alloy compositions, these are, for example, the elements iron, nitrogen and oxygen. Carbon or hydrogen impurities are also possible. Thus, the thermal spray coating of the present invention can have the corresponding impurities, in particular the elements mentioned above. The elements oxygen, iron and nitrogen are preferably present in the thermal spray coating according to the invention in the following maximum amounts: less than 1000 μg / g oxygen, less than 500 μg / g iron and less than 200 μg / g nitrogen. For oxygen, the preferred content is less than 500 μg / g, more preferably less than 250 μg / g, particularly preferably the oxygen content of the coating is between 5 and 210 μg / g. The nitrogen content is preferably less than 200 μg / g nitrogen, more preferably less than 100 μg / g nitrogen. The nitrogen content is particularly preferably between 0.5 and 50 μg / g. The oxygen and nitrogen contents in the thermal spray coating should be kept as low as possible. On the one hand, this can have an advantageous effect on the processability of the powder for the thermal spray coating. On the other hand, pore formation in the thermal spray coating is avoided. The iron content should be as low as possible, preferably less than 500 μg / g. More preferably, the iron content is less than 250 μg / g. The iron content of the coating is particularly preferably 100 μg / g or less, and most preferably 0.5 to 50 μg / g, because Fe dissolved in Cu or Cu alloy reduces the electrical conductivity of the thermal spray coating.

[0016] The thermal spray coating according to the invention preferably has a relative density of 95% or more, in particular 97% or 98% or more, of the theoretical density of Cu or Cu-based alloy. Thus, pores can also be present in the coating, with a porosity of 2% or less, but preferably less than 1.5%. A high relative density ensures a high electrical conductivity. The determination of density follows Archimedes' principle, which describes the relationship between the mass, volume and density of a solid immersed in a liquid. Using the so-called buoyancy method, the weight reduced by buoyancy is determined, and the density is calculated from this and the weight in air. The relative density is the density measured relative to the theoretical density of the respective material. The theoretical density of a material corresponds to the density of a 100% dense material without pores. In the present invention, the carrier body is ground after the thermal spray coating to determine the density, so that only the coating remains and can be measured.

[0017] The thermal spray coating can extend over the entire or partial carrier body. In addition to the carrier body, the thermal spray coating can also cover parts of the rotor adjacent to the carrier body. These parts can be connected to the carrier body, for example, by a material bond or a form fit.

[0018] According to the invention, the carrier body is material-bonded to the thermal sprayed coating at least partially via the connection surface, which is located between a surface or a region of the surface of the carrier body and a surface or a region of the surface of the thermal sprayed coating and connects the carrier body to the thermal sprayed coating with a material bond, so that the carrier body is permanently and inseparably connected to the thermal sprayed coating.

[0019] The rotor part according to the invention does not have a transition zone on the connection surface between the carrier body and the thermal spray coating.

[0020] According to the prior art, the transition zone is a zone of molten interface or a diffusion zone, which may occur at the transition between the material of the carrier body and the material of the coating, for example when backcasting the carrier body with Cu or a Cu alloy. The material is melted on the surface of the carrier body, for example by high temperature, and diffuses into the coating. The material of the coating also diffuses into the carrier body. For example, the Cu layer and the Fe layer may form a common layer in the intermediate transition zone (with a composition gradient, typically with a high Fe content towards the side of the Fe layer and a high Cu content towards the side of the Cu layer), i.e. typically there is no homogeneous material in the transition zone. Such a transition zone is usually formed during backcasting, as described above.

[0021] "Without transition zone" means that the surface structure of the substrate and the surface structure of the sprayed coating can be clearly defined, i.e. the two materials are directly adjacent to each other at the joint interface. Basically, there is no mass transfer between the two materials, i.e. any transition zone that may exist is no longer detectable or does not exist at all. The surface structure of the carrier body may still have a slight surface roughness (Ra) or surface irregularities at the connection surface (see FIG. 4a). Such a surface roughness does not represent a transition zone, since the material of the carrier body can still be clearly defined from the sprayed coating. The roughness of the surface can be measured tactilely or optically. In the case of tactile measurement, the surface is measured with a measuring probe for roughness measurement using the tactile step method (line roughness) according to DIN EN ISO 4287.

[0022] The invention described herein eliminates the drawbacks identified by the inventors with regard to the transition zone formed between the carrier body and the coating during backcasting. Furthermore, there is no contamination of the coating with dissolved carrier material. The properties of the material in the coating, such as the electrical conductivity of copper, are significantly impaired both by the occurrence of the transition zone and by possible impurities. As already explained above, "without transition zone" means that the material of the sprayed coating is directly adjacent to the material of the substrate at the joining surface. As a result, the electrical conductivity of the joining surface is determined only by the material of the sprayed coating and the material of the carrier body, but is not adversely affected by the transition zone or impurities in the coating, which typically have a lower electrical conductivity. Furthermore, sprayed coatings have the advantage that the thickness of the coating is small compared to the backcasting process, and more complex geometries can also be taken into account for rotor parts that do not necessarily have to be rotationally symmetric.

[0023] In a preferred embodiment of the invention, the sprayed coating is a cold gas sprayed (CGS) coating. When the sprayed coating is applied to the substrate by cold gas spraying, it can be seen under a microscope that the coating consists of individual particles. The particles in the coating applied by cold irradiation do not show a molten phase and are still clearly recognizable in the deposited coating. The particles undergo deformation due to the high kinetic impact energy, so that the coating contains cold-formed Cu particles or Cu-based alloy particles at least in some areas. Cold deformation should be understood by metallurgical definition as the particles are deformed by impact with the substrate under conditions (temperature / time) that do not lead to recrystallization. Cold-worked structures are characterized by characteristic dislocation structures, as is well known to any specialist and described in detail in specialist texts. The dislocation structures can be visualized, for example, using a TEM (Transmission Electron Microscope).

[0024] The cold-formed particles of the coating are at least partially elongated in a direction parallel to the surface of the substrate (transversely), whereby the average (average value of at least 100 elongated particles) particle aspect ratio (GAR; corresponding to the particle's length divided by its width) is greater than 1. The aspect ratio is determined metallographically by analyzing the images using the Linear Section Method (Linienschnittverfahren) (see ASTM E112-96). For this purpose, a part embedded in an embedding agent, for example an epoxy resin, is first produced. After a curing time, the sample is metallographically prepared, i.e. the cross section can be analyzed later. The preparation comprises the following steps: grinding, for example with bonded SiC paper with a grit size between 220 and 1200; polishing with a diamond suspension with a grit size of 3 μm; final polishing with OPS (oxide polishing suspension) with a grit size of 0.04 μm; cleaning the sample in an ultrasonic bath and drying the sample. The cross section is then etched. A scanning electron microscope is used to determine the aspect ratio by the width-to-height ratio of the particles.

[0025] In a further embodiment of the invention, the thermal spray coating is recrystallized or recovered by annealing after low-temperature spray coating, resulting in a fine-grained, more equiaxed microstructure that is significantly different from backcast coatings. After annealing, the low-temperature spray coating shows a recrystallized microstructure of Cu particles or Cu-based alloy particles with an average grain size of 150 μm or less, preferably 100 μm or less, more preferably 50 μm or less, particularly preferably 1 μm to 10 μm. The average grain size can be easily analyzed using the line cut method on optical microscope images of longitudinal metallographic sections (the forming direction and the normal direction form the image plane). For this purpose, the longitudinal sections are prepared by etching in order to visualize the grain boundaries. At a magnification of 500 times (image section 240 × 100 μm), five lines are placed in the image at equal intervals from edge to edge, the maximum grain size is measured in both directions (forming direction and normal direction) and the average value ((a + b) / 2) is taken. The recrystallization increases the electrical conductivity of the rotor component according to the invention. Furthermore, the adhesion of the copper or Cu-based alloy layer to the carrier material is improved.

[0026] The thickness of the sprayed coating is preferably 0.025 mm to 5 cm. In particular, the thickness is advantageously 0.1 mm to 4 mm, more preferably 0.5 mm to 2 mm, particularly preferably 0.8 mm to 1.2 mm. The layer can consist of a single layer or preferably several layers. The layer thickness can be determined using a scanning electron microscope. Metallographic sections are taken perpendicular to the plane of the intermediate layer and the layer thickness is then measured under a scanning electron microscope at an appropriate magnification. The layer thickness should be determined at a representative point on the section. At least 10 different representative points should be analyzed for their coating thickness and an average value should be determined, which provides the value of the average thickness of the coating.

[0027] According to a further advantageous embodiment of the invention, the thermal spray coating has a conductivity of 26 MS / m (megasiemens per meter) or more. Preferably, the conductivity is 40 MS / m or more, more preferably 50 MS / m or more, particularly preferably 55 MS / m or more. The conductivity is measured according to DIN EN 16813 (2017).

[0028] The rotor part according to the invention exhibits good adhesion strength of the thermal spray coating. The adhesion strength was measured according to ASTM C633-13 (2016). The adhesion strength of the rotor part according to the invention is more than 10 MPa, preferably more than 20 MPa.

[0029] The invention also relates to a method for manufacturing a rotor part for an X-ray rotating anode having a carrier body and a thermal spray coating, the method being characterized by the following steps: - providing a support comprising a heat resistant metal, a heat resistant metal-based alloy, Fe, an Fe-based alloy or a combination thereof; - coating a carrier with a thermal spray coating using a powdered coating material, thereby producing a rotor component having at least a partially material-bonded connection at the connection surface between the carrier body and the thermal spray coating, wherein the thermal spray coating consists of Cu or a Cu-based alloy, and the microstructure of the rotor component does not have a transition zone at the connection surface between the carrier body and the thermal spray coating.

[0030] With the method according to the invention for producing a rotor part, the advantages mentioned above with respect to the part according to the invention are achieved reliably and with process reliability. Furthermore, the advantageous embodiments of the invention mentioned above are also advantageous for the method according to the invention.

[0031] It is particularly preferred that the thermal spray coating is applied using cold gas spraying (CGS). As mentioned above, powder particles with very high kinetic energy and low thermal energy are applied to the carrier body. A process gas under high pressure (e.g. air, helium (He), nitrogen (N2), water vapor or mixtures thereof) is expanded using a convergent-divergent nozzle (also known as a supersonic nozzle). A typical nozzle shape is a Laval nozzle. Depending on the process gas used, gas velocities of 300 to 1200 m / s (meters per second) (for N2) or up to 2500 m / s (for helium) can be achieved. The coating material is injected into the gas stream, for example upstream of the narrowest cross section of a convergent-divergent nozzle forming part of the spray gun, accelerated to a speed of typically 300 to 1200 m / s and deposited on the carrier body. By heating the gas upstream of the convergent-divergent nozzle, the gas flow velocity and therefore the particle velocity also increase as the gas expands in the nozzle. Typically, gas temperatures from room temperature (RT), in particular 20° C., to 1000° C. are used for low-temperature gas spraying according to the invention. Low-temperature gas spraying can be used in particular to spray ductile materials with face-centered cubic and hexagonal close-packed lattices to form dense, well-adhering layers. Typically, low-temperature irradiation is used to apply metal layers to metal substrates. In low-temperature gas spraying, the coating is built up layer by layer from individual particles of the coating material. The adhesion of the coating material to the substrate and the cohesion between the coating material particles are crucial for the quality of the low-temperature gas sprayed coating. In principle, the adhesion is a combination of several physical and chemical adhesion mechanisms, both in the area of ​​the bonding surface of the coating material / substrate and between the coating material particles. Due to the low process temperature, the powder does not melt during low-temperature gas spraying, but instead impinges on the substrate to be coated in a non-molten state, building up a layer. The high kinetic energy resulting from the high velocity of the powder moving through the gas stream causes a mechanical interlock when the powder strikes the surface of the substrate, the interlock being assisted by the process temperature. Coatings produced in this way using low temperature gas spraying can be recognized under a microscope by the fact that the coating consists of individual particles having a "pancake" shape (i.e. a structure in which the length and width of the individual particles are large compared to their thickness).The particles are deformed by the high kinetic impact energy and exhibit an aspect ratio greater than one.

[0032] According to an advantageous production method of the invention, the low-temperature gas spraying is carried out at a pressure of 10 to 100 bar, preferably 20 to 80 bar, particularly preferably 30 to 60 bar, and at a gas temperature of room temperature (RT) to 1000°C (room temperature is in particular 20°C). The gas temperature is preferably 300 to 1000°C, particularly preferably 400 to 800°C.

[0033] According to an advantageous manufacturing method of the invention, the rotor part is annealed in vacuum or in a protective gas atmosphere after the coating step. This process step improves the electrical conductivity of the coating and reduces residual stresses in the coating. Preferably, the rotor part is annealed at 400-750°C for up to 5 hours. More preferably, it is annealed at 500-600°C for 0.5-3 hours.

[0034] According to an advantageous manufacturing method of the invention, the carrier body is surface-treated before the coating step. This can be a chemical or physical surface treatment. It can be a surface treatment with alcohol, blasting, etc. Surface treatment with a powder jet is preferred, which allows for better adhesion of the low-temperature spray coating to the substrate.

[0035] The method according to the invention as well as preferred embodiments thereof achieve, inter alia, the following advantageous effects: - Improved electrical conductivity of thermally sprayed coatings on rotor components; - Reduction of layer residual stresses and improvement of adhesion of thermal spray coatings; - the absence of a transition zone between the carrier body and the thermal sprayed coating, which improves the electrical conductivity at the connecting surface between the carrier body and the thermal sprayed coating.

[0036] Coating materials are composed of particles. A large number of particles is called a powder. A large number of powder particles can be transformed into powder granules by granulation. The size of the powder particles or powder granule particles is called the particle size and is usually measured using laser diffraction methods. The measurement results are given as a distribution curve. d 50The values ​​indicate the average particle size. 50 means that 50% by volume of the particles are smaller than the specified value.

[0037] Furthermore, the particle size d is 5 μm or more and 150 μm or less. 50 It is advantageous to have d 50 is measured by laser diffraction method using standard (ISO 13320-2009). Another advantageous range is 10 μm≦d 50 ≦100μm or 15μm≦d 50 ≦80 μm.

[0038] According to an advantageous manufacturing method of the invention, the spray coating can be applied in several layers of powdered Cu or several layers of powdered Cu-based alloy. The final thickness of the coating is between 25 μm and 5 cm. The thickness of the coating is determined using conventional metallographic methods.

[0039] Further advantages and benefits of the present invention will be apparent from the following description of the embodiments with reference to the accompanying drawings. [Brief description of the drawings]

[0040] [Figure 1] Schematic diagram of a longitudinal section of a state-of-the-art X-ray tube with a rotating X-ray anode [Diagram 2] Scanning electron microscope image of the transition zone between the steel body and the copper in sample no. 1 using state-of-the-art technology (magnification 100x) [Diagram 3] Scanning electron microscope image (magnification 100x) of the transition zone between the steel body and the copper in sample No. 2 according to the invention [Figure 4a] Scanning electron microscope image (magnification 500x) of the transition zone between the steel body and the copper in sample No. 2 according to the invention [Figure 4b] Scanning electron microscope image of the transition zone between the steel body and copper in sample no. 1 using state-of-the-art technology (magnification 500x) [Figure 4c] Line scan of the transition zone between the steel body and copper based on Fig. 4(b) [Diagram 5]Scanning electron microscope image (magnification 100x) of the copper coating on sample No. 2 according to the invention before the annealing step [Figure 6] Optical microscope image (magnification 200x) of the copper coating on sample number 2 according to the invention after etching and before the annealing step [Figure 7] Optical microscope image (magnification 200x) of the copper coating on sample No. 2 according to the invention after etching and annealing steps [Figure 8] Optical microscope image (magnification 50x) of the copper coating on sample No. 2 according to the invention after etching and after annealing [Figure 9] Optical microscope image of the copper coating on sample no. 1 using state-of-the-art techniques after etching (magnification 50x)

[0041] FIG. 1 shows a longitudinal section of an X-ray tube with a rotor and an X-ray rotating anode, as known in the prior art. An X-ray tube usually consists of a glass bulb (5) with a vacuum interior (4). The glass bulb contains a cathode (3) with a heating coil (6) that emits electrons (7). Opposite the cathode (3) is the X-ray rotating anode (2), which comprises an anode disk (11) connected by a shaft (12) to the rotor (1) of an electric motor. A stator (9, 10) is arranged outside the glass bulb (5) to drive the rotor. When connected to electricity, the stator (9, 10) generates a magnetic field that rotates around the glass bulb (5), which exerts a torque on the rotor (1) and thus the X-ray rotating anode (2). The rotor (1) and the X-ray rotating anode (2) are arranged in a high vacuum (4) in a glass flask (5). Electrons (7) emitted by the cathode (3) are accelerated towards the anode disk and, upon striking the anode disk, decelerate to produce X-rays (8), which exit the X-ray tube through an emission window in the glass bulb.

[0042] [Example] Sample No. 1 was manufactured using a backcasting process according to the state of the art. A steel tube of length 103 mm, outer diameter 62 mm and inner diameter 44 mm was provided for this purpose with the composition 0.08-0.15 wt% C, 1.00 wt% Si, 1.50 wt% Mn, 0.040 wt% P, 0.030 wt% S, 11.5-13.5 wt% Cr, balance Fe and normal impurities. This steel tube was inserted into a graphite mould and then backcast with a copper melt (containing at least 99.95 wt% Cu, the balance being normal impurities totalling up to 0.05 wt%). The steel tube was then ground so that the copper coating (on the outer sheath surface of the steel tube) had a thickness of 2 mm.

[0043] For sample number 2 of the present invention, a Cu powder was prepared having 99.95 atomic % Cu and 28 μg / g C, less than 10 μg / g Fe, 4 μg / g H, less than 5 μg / g N, and 201 μg / g O. The average particle size d 50 The thickness of the steel was 26.53 μm. A steel part with a diameter of 25 mm and a height of 7 mm was prepared with a composition of 0.20-0.22 wt% C, 0.55 wt% Si, 1.60 wt% Mn, 0.025 wt% P, 0.025 wt% S, 0.55 wt% Cu, with the balance Fe and normal impurities, and the surface was pre-cleaned. The steel part was then coated with Cu powder using a low-temperature gas spray process. The following low-temperature gas spray process parameters were used: pressure 32 bar, gas temperature 400°C, process gas N2. After coating, the sample was annealed in high vacuum at 550°C for 1 hour. The coating was ground down to 1 mm, leaving a total thickness of 8 mm for the sample.

[0044] The electrical conductivity of the coating was then measured according to DIN EN 16813 (2017). Sample No. 1 had a conductivity of 24 MS / m. Sample No. 2 had a conductivity of 56 MS / m. For pure copper, the electrical conductivity is 58 MS / m (according to IACS). As a result, the cold gas spray coated steel parts have almost twice the electrical conductivity of steel parts produced by backcasting. In addition, the samples according to the invention have an electrical conductivity almost equivalent to that of pure copper.

[0045] Also, the adhesive strength of the copper sprayed coating film to the steel part of sample number 2 was tested. Also, the adhesive strength of the copper sprayed coating film to the steel part of sample number 2 was tested.

[0046] To analyze the interface and the applied coating, polished sections were made whose image surface was at a 90° angle to the coating surface, thus depicting the two base materials and their interfaces. These polished sections were examined under a scanning electron microscope at 100x and 500x magnifications, and images were taken. Meanwhile, optical microscope images of the polished sections were also taken, and the sections were pre-etched to show the grain structure of the thermal sprayed coating.

[0047] FIG. 2 shows the transition from steel to copper coating in a cross-sectional slice of sample no. 1 of the state-of-the-art example (Cu backcasting on steel) in a scanning electron microscope image at 100x magnification. FIG. 2 shows the steel body (A, dark areas) in the lower half of the image and the copper coating (C, light areas) in the upper half of the image. The copper coating is bonded to the steel over the entire surface via the transition zone (B) and the loosening of the steel surface by the copper backcasting is clearly visible. The transition zone (B) shows an approximate thickness of about 50 μm. It can be clearly seen that the copper coating penetrates the steel surface and that steel components are also present in the copper coating, i.e. both materials diffuse between each other and there is no homogeneous material property in the transition zone.

[0048] Figure 3 shows the transition from steel to copper coating in a cross-sectional section of sample number 2 of an example according to the invention (low-temperature gas spray coating on steel) at 100x magnification in a scanning electron micrograph. Figure 3 shows the steel body (A, dark areas) in the lower half of the image and the copper coating (C, light areas) in the upper half of the image. Bonding of the copper coating to the steel is complete over the entire surface and no intermixing of the materials can be discerned, i.e. there is no transition zone.

[0049] FIG. 4a is an enlarged image of FIG. 3 and shows the transition from steel to copper coating in a cross-sectional slice of sample number 2 of an embodiment according to the invention (low-temperature gas spray coating on steel) at 500 times magnification in a scanning electron microscope image. FIG. 4a shows the steel body (A, dark areas) in the lower half of the image and the copper coating (C, light areas) in the upper half of the image. The surface of the steel is clearly recognizable and shows irregularities. These irregularities can be caused either by the surface treatment of the steel before low-temperature irradiation or by the impingement of copper on the steel surface. In the shown figure, the surface irregularities reach up to 10 μm. However, it is clearly visible that the steel surface is not melted and no intermixing of the materials has occurred. There is a clear boundary between the steel body (A) and the copper coating (C).

[0050] Figure 4b is an enlarged image of Figure 2 and shows the transition from steel to copper coating in a cross-sectional slice of sample number 1 of the state-of-the-art example (backcasting on steel) in a scanning electron microscope image at 500x magnification. Figure 4b shows the steel body (A, dark area) in the right half of the image and the copper coating (C, light area) in the left half of the image. The transition zone (B) is clearly visible. Copper has partially penetrated deep into the steel surface. The steel surface shows clear signs of melting, which means that steel is present in the copper layer.

[0051] Figure 4c shows a line scan of the copper to steel transition zone according to Figure 4b. For this purpose, the elemental concentrations of the elements chromium, iron and copper are measured along a line starting from the copper coating (C, light area) and heading towards the steel body (A, dark area). The peak intensities after excitation with the Cu K(α) radiation used for the evaluation are iteratively corrected for atomic number, absorption and fluorescence in this method, thus allowing a quantitative calculation of the elemental composition (atomic %) without the use of standards. In the region of the transition zone (B), it is clearly visible that a large amount of iron is present in the copper coating and that a large amount of copper penetrates deep into the surface of the steel body. The high Cu content in the region of the Cu layer (C) before the transition zone (B) and the high Fe content in the steel body (A) after the transition zone (B) can be clearly recognized. In the region of the Cu layer (C), a higher Fe content is also recognizable (especially compared to the Cu content in the steel body (A)). This shows that Fe can also penetrate beyond the transition zone into the Cu coating (C). It can also be seen that the steel body contains a certain percentage of chromium.

[0052] Figure 5 shows the copper coating before the annealing step in a cross-sectional section of sample number 2 of an example according to the invention (low-temperature spray coating on steel) at a magnification of 500x in a scanning electron microscope image. The copper coating shows a homogeneous layer with a density of more than 97% (97-98.66%) of the theoretical density of copper. Individual layers are not discernible.

[0053] Figure 6 shows the copper coating (C) before the annealing step in a cross-sectional section of sample number 2 of an example according to the invention (low-temperature gas spray coating on steel) at 200x magnification in an optical microscope image. The grain boundaries were highlighted by etching the Cu particles so that the microstructure was clearly visible. The elongated shape of the Cu particles and many layers can be recognized. This coating is clearly different from the Cu coating using backcasting (see Figure 9).

[0054] Figure 7 shows the copper coating (C) after the annealing step in a cross-sectional section of sample number 2 of the example according to the invention (low-temperature gas spray coating on steel) at a magnification of 200x in an optical microscope image. The grain boundaries were highlighted by etching the Cu particles so that the microstructure is clearly visible. A fine-grained, equiaxed microstructure of the coating can be recognized.

[0055] FIG. 8 shows the copper coating (C) after the annealing step in a cross-sectional section of sample number 2 of an example according to the invention (low-temperature gas spray coating on steel) at 50x magnification in an optical microscope image. This low magnification was chosen for a direct comparison with the grain size in the backcasting process. After etching the Cu particles, the fine and uniform microstructure of the copper coating (C) can be recognized. Also the steel body (A, dark area) can be recognized.

[0056] Figure 9 shows the copper coating (C) in a cross-sectional section of sample no. 1 of the state-of-the-art example (Cu backcasting on steel) in an optical microscope image at a magnification of 50x. The formation of a large grain structure of the copper coating during backcasting is clearly visible after etching the copper particles.

Claims

1. 1. A rotor part for an X-ray rotating anode, comprising a carrier body and a thermal sprayed coating, the carrier body being made from one of the group of materials consisting of a heat-resistant metal, a heat-resistant metal-based alloy, Fe, an Fe-based alloy or a combination thereof, the thermal sprayed coating being made from Cu or a Cu-based alloy, the carrier body being material-bonded to the thermal sprayed coating in at least some parts at a connection surface, characterized in that the microstructure of the rotor part does not have a transition zone at the connection surface between the carrier body and the thermal sprayed coating.

2. The rotor component of claim 1 , wherein the thermal spray coating is a low-temperature gas thermal spray coating.

3. 3. The rotor component according to claim 2, characterized in that the low-temperature gas spray coating comprises cold-formed Cu particles or Cu-based alloy particles which are at least partially elongated parallel to the surface of the carrier body and have an elongation ratio of more than 1, at least in certain regions.

4. The rotor component according to claim 2, characterized in that the low-temperature gas spray coating after annealing has a recrystallized microstructure of the Cu particles or the Cu-based alloy particles with an average grain size of 150 μm or less.

5. The rotor component according to any one of claims 1 to 4, characterized in that the composition of the Cu sprayed coating film or the Cu-based alloy sprayed coating film contains 1000 μg / g or less of oxygen, 500 μg / g or less of iron, and 200 μg / g or less of nitrogen.

6. The rotor component according to any one of claims 1 to 5, characterized in that the thermal spray coating has a layer thickness of 25 µm to 5 cm.

7. The rotor component according to any one of claims 1 to 6, characterized in that the thermal spray coating of the rotor component has a conductivity of 26 MS / m or more in the coating.

8. The rotor component according to any one of claims 1 to 7, wherein the thermal spray coating has a density of 90% or more of the theoretical density of the Cu or Cu-based alloy.

9. A method for manufacturing a rotor part for an X-ray rotating anode comprising a carrier body and a thermal spray coating, the method being characterized by the following steps: Providing a support comprising a refractory metal, a refractory metal-based alloy, Fe, an Fe-based alloy, or a combination thereof. - coating the carrier body by thermal spray coating with a powdered coating material to produce a rotor component having an at least partially material-bonded connection at the connection surface between the carrier body and the thermal spray coating, wherein the thermal spray coating consists of Cu or a Cu-based alloy and the microstructure of the rotor component has no transition zone at the connection surface between the carrier body and the thermal spray coating.

10. The method of claim 9, wherein the thermal spray coating is applied by low temperature gas spraying.

11. A method according to claim 10, characterized in that the low temperature gas spraying is carried out at a pressure between 10 and 100 bar and at a gas temperature between room temperature and 1000°C.

12. Method according to any one of claims 9 to 11, characterized in that the rotor part is annealed in vacuum or in a protective gas atmosphere after the coating step.

13. A process according to any one of claims 9 to 12, characterised in that the rotor part is annealed after the coating step at 400-750°C for up to 5 hours.

14. A method according to any one of claims 9 to 13, characterized in that the carrier body is surface treated prior to the coating step.

15. The method according to any one of claims 9 to 14, characterized in that the powdered coating material of Cu or Cu-based alloy has a powder grain size of 5 to 150 μm.

Citation Information

Patent Citations

  • Rotor for X-ray tube rotary anode

    DE19945414A1

  • Method of manufacturing rotor of induction motor

    JP2002142421A

  • Method for coating substrates and coated products

    JP2010509502A